Beban Kerja, Burn Out, Jenjang Karir, Employee Engagement terhadap Loyalitas Karyawan Pada Kantor Kelurahan Harapan Jaya Bekasi Utara - Nawang Dwi Anjani; Dewi Puspaningtyas Faeni; Novita Wahyu Setyawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to determine workload, burn out, career path, employee engagement on employee loyalty at the Harapan jaya village office, North Bekasi. Using a descriptive quantitative approach method by distributing a 1-5 Likert scale. The employee population is 65 employees and the sample used was 65 samples. Research using Smart PLS 3.0 software. The results of this study the workload variable has a P-Values value of 0.731 or <0.05, so it can be stated that workload has a significant negative effect on employee loyalty. The burn out variable has a P-Values value of 0.759 or <0.05, workload has a significant negative effect on employee loyalty. The career path variable has a P-Values value of 0.012 or <0.05, workload has a significant positive effect on employee loyalty. The employee engagement variable has a P-Values value of 0.022 or <0.05, workload has a significant positive effect on employee loyalty. While the results of simultaneous research from workload variables, burn out, career path, employee engagement are positive and significant to employee loyalty with an F-count value of 26. 425> F-table 1.40 and the coefficient of determination (R2) on R-Square obtained a value of 56.7%. Keywords: Workload, Burn Out, Career Path, Employee Engagement, Employee Loyalty